2011
DOI: 10.1016/j.joca.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Complex loading affects intervertebral disc mechanics and biology

Abstract: Background Complex loading develops in multiple spinal motions and in the case of hyperflexion is known to cause intervertebral disc (IVD) injury. Few studies have examined the interacting biologic and structural alterations associated with potentially injurious complex loading, which may be an important contributor to chronic progressive degeneration. Objective This study tested the hypothesis that low magnitudes of axial compression loading applied asymmetrically can induce IVD injury affecting cellular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
143
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(162 citation statements)
references
References 47 publications
10
143
1
Order By: Relevance
“…Apart from in vitro studies, organ cultures of bovine caudal IVDs have shown that compression induces apoptosis, produces inflammatory mediators and alters matrix integrity, leading to development of the disease [96].…”
Section: Mmp19mentioning
confidence: 99%
“…Apart from in vitro studies, organ cultures of bovine caudal IVDs have shown that compression induces apoptosis, produces inflammatory mediators and alters matrix integrity, leading to development of the disease [96].…”
Section: Mmp19mentioning
confidence: 99%
“…Therefore, model organisms, such as the cow, are used for in vitro cellular and ex vivo biomechanical studies of the IVD [14,15]. The bovine tail IVD represents a good model for the non-degenerate human IVD: the bovine NP retains few notochordal cells and whole transcriptome analyses identified similar phenotypic marker genes as in humans [6,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The disc -particularly the nucleus -becomes less gelatinous and more fibrous, and cracks and fissures eventually form. In AIS patients, minor histological alterations of the disc can be observed as soon as 3-7 years of age and they significantly increase after 16 years of age [8]; asymmetric loading, which is characteristic of scoliosis, can add to the detrimental effects of aging on disc biology [9].…”
Section: Introductionmentioning
confidence: 99%